Analisis Tingkat Kemampuan Mahasiswa dalam menghadapi Deadline Penugasan Akademik - Rachel Nanda Herlina; Naura Nurfaida Rahma; Shifa Pujaningtyas; Keisha Putri Azzahra; Joko Tri Nugraha (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Academic deadlines are one of the main challenges faced by university students in managing their learning activities effectively. Poor time management often leads to academic procrastination, which may reduce assignment quality and increase academic stress. This study aimed to analyze the influence of academic procrastination and students’ perceptions of assignment deadlines on time management among students of the Faculty of Social and Political Sciences at Universitas Tidar. The research employed a quantitative descriptive approach involving 131 students selected through simple random sampling. Data were collected using an online questionnaire with a Likert scale and analyzed using descriptive statistics and hypothesis testing with SPSS software. The findings showed that academic procrastination had a significant effect on students’ time management (t = 18.139; p < 0.001). In addition, students’ perceptions of deadline impact on assignment quality also significantly influenced time management (t = 22.018; p < 0.001). Simultaneously, both variables significantly affected students’ ability to manage academic deadlines (F = 292.475; p < 0.001). These results indicate that effective time management plays an important role in reducing procrastination and improving students’ academic performance.